Changing epidemiology and outcomes of acute kidney injury in Brazilian patients: a retrospective study from a teaching hospital - Ponce, Daniela [UNESP]; Zamoner, Welder [UNESP]; Batistoco, Marci Maira [UNESP]; Balbi, André [UNESP] (Springer Nature, 2020)
Purpose: While considerable information is available on acute kidney injury (AKI) in North America and Europe, large comprehensive epidemiologic studies on AKI from Latin America and Asia are still lacking. The present study aimed to evaluate the epidemiology and outcomes of AKI in patients evaluated by nephrologists in a Brazilian teaching hospital. Methods: We performed a large retrospective observational study that looked into the epidemiology of AKI and its effect on patient outcomes across time periods. For comparison purposes, patients were divided into two groups according to the year of follow up: 2011–2014 and 2015–2018. Results: We enrolled 7976 AKI patients and, after excluding patients with chronic kidney disease stages 4 and 5, kidney transplant recipients and those with incomplete data, 5428 AKI patients were included (68%). The maximum AKI stage was 3 (50.6%), and there was a mortality rate of 34.3% (1865 patients). Dialysis treatment was indicated in 928 patients (17.1%). Patient survival improved along the study periods, and patients treated in 2015–2018 had a relative risk death reduction of 0.89 (95% CI 0.81–0.98, p = 0.02). The independent risk factors for mortality were sepsis, > 65 years of age, admission to the intensive care unit, AKI-KDIGO 3, recurrent AKI, no metabolic and fluid demand to capacity imbalance (as a dialysis indication), and the period of treatment. Conclusion: We observed an improvement in AKI patient survival over the years, even after correction for several confounders and using a competing risk approach. Identification of risk factors for mortality can help in decision-making for timely intervention, leading to better clinical outcomes.
Keywords: Acute kidney injury; Epidemiology; Outcome; Period